Predictors of neurodevelopment outcomes among children under 5 years old in Nairobi informal settlements - Amboka, Patrick; Nampijja, Margaret; Masibo, Peninah (Frontiers in Neuroscience, 2025)
BackgroundA child’s early years of life are a critical period for brain development, and malnutrition at this stage is associated with irreversible developmental delays. Developmental delays can be affected by maternal, child, and household factors. This study examined the association between acute malnutrition relapse and neurodevelopmental outcomes among children under 5 years old in Nairobi’s informal settlements.MethodologyThe study used a comparative cross-sectional design that was hospital-based and was carried out in Viwandani and Korogocho informal settlements in Nairobi, Kenya. The three groups that were compared were children under 5 years old who had never suffered acute malnutrition, those who had the first episode of acute malnutrition, and those who had acute malnutrition relapse. Relapse in acute malnutrition was defined as wasting within 6 months after exiting treatment, as per the recommended discharge criteria (Council of Research and Technical Advice for Acute Malnutrition, CORTASAM). The study used both quantitative and qualitative methods, and the purposive sampling technique was used in both methods. The Malawi Development Assessment Tool (MDAT) assessed the neurodevelopment outcomes. Quantitative data is presented at the univariate, bivariate, and multivariate levels. Qualitative data were analyzed thematically, and predetermined themes and emerging themes were identified and added.ResultsAcute malnutrition relapse was a significant predictor of neurodevelopment outcomes among children under 5 years old. Children who had either never relapsed from acute malnutrition or had normal nutrition status were 2.08 times more likely to have normal neurodevelopmental outcomes compared to children who had relapsed [AOR = 2.08; CI:1.11, 3.90; p-value, 0.02]. Maternal postpartum depression and child maturity status at birth were also significant predictors of neurodevelopmental outcomes among children under 5 years in Nairobi informal settlements [AOR = 3.62; CI:1.86, 7.04; p-value < 0.001], [AOR = 2.93; CI:1.21, 7.12; p-value, 0.02], respectively. The qualitative findings further showed that breastfeeding, sanitation, and diarrhea have an association with children’s neurodevelopmental outcomes.ConclusionThis study demonstrates that children under five who experience relapses due to acute malnutrition exhibit significantly delayed neurodevelopmental outcomes compared to those who do not relapse. Furthermore, qualitative findings showed that breastfeeding, sanitation, and diarrhea have an association with children’s neurodevelopmental outcomes.